2022
DOI: 10.3389/fmed.2022.848202
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychosomatic and Genitourinary Syndrome Among Menopausal Women: A Systematic Review and Meta-Analysis

Abstract: IntroductionThe menopausal transition represents the passage from reproductive to non-reproductive life and is characterized by a number of menstrual disturbances. We systematically reviewed the evidence on the prevalence of psychosomatic and genitourinary syndrome among menopausal women and compared the risk of symptoms between premenopausal, perimenopausal, and post-menopausal women.MethodsWe performed a systematic search in MEDLINE, CINAHL, and ScienceDirect through March 2021. Case series/reports, conferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
1
9
0
2
Order By: Relevance
“…Research Freeman et al (2008) found a positive correlation indicating that a woman will feel more stressed when experiencing disturbing menopausal symptoms. Symptoms experienced during menopause include vasomotor, psychosomatic, and psychological symptoms (Augoulea et al, 2019;Hazlina et al, 2022;Sood et al, 2019;Yadav et al, 2021). Shringarpure et al (2022) found the results of a study of 145 women in urban and rural areas, most of them experienced psychosomatic symptoms such as physical exhaustion-fatigue, sleep problems, difficulty climbing stairs, hot flushes, and body aches.…”
Section: Introductionmentioning
confidence: 99%
“…Research Freeman et al (2008) found a positive correlation indicating that a woman will feel more stressed when experiencing disturbing menopausal symptoms. Symptoms experienced during menopause include vasomotor, psychosomatic, and psychological symptoms (Augoulea et al, 2019;Hazlina et al, 2022;Sood et al, 2019;Yadav et al, 2021). Shringarpure et al (2022) found the results of a study of 145 women in urban and rural areas, most of them experienced psychosomatic symptoms such as physical exhaustion-fatigue, sleep problems, difficulty climbing stairs, hot flushes, and body aches.…”
Section: Introductionmentioning
confidence: 99%
“…Genitourinary syndrome of menopause (GSM), formerly known as vulvovaginal atrophy and atrophic vaginitis, includes urinary symptoms (e.g., recurrent urinary tract infections, dysuria, and urgency), sexual symptoms (e.g., impaired function, pain or discomfort, and lack of lubrication), and genital symptoms (e.g., irritation, dryness, and burning; Marino, 2021). Reports suggest this syndrome affects more than 50% of postmenopausal women (Marino, 2021; Nik Hazlina et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of negative moods, depressive and anxiety symptoms are the two major psychological manifestations during perimenopause. A recent systematic review and meta-analysis showed that the overall prevalence of psychological symptoms for perimenopausal women is 42.1% 12. Genitourinary syndrome of menopause is another concern in relation to sexual and reproductive health, which also draws increasing attention in geriatrics globally 13.…”
Section: Introductionmentioning
confidence: 99%